Cement-based composite material mixed with surface-modified steel fibers and preparation method of cement-based composite material

By functional modification of biophenol hydroxy acids and layer-by-layer mineralization treatment on the surface of steel fibers, combined with the use of zinc oxide whiskers, the problems of uneven dispersion and poor binding force of steel fibers are solved, and the mechanical properties of concrete are significantly improved and Durability.

CN119118603AActive Publication Date: 2024-12-13THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +3
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411317742.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The dispersion of steel fibers in existing ultra-high performance concrete is uneven, resulting in the inadequate utilization of the reinforcement effect and poor binding force, which affects its service life and brittleness characteristics.

Method used

By functional modification of biophenol hydroxy acids and mineralization layer by layer on the steel fiber surface, nanoparticles are introduced to form a stable composite network structure, improving the interface bonding stress between steel fibers and cement matrix, and reducing zinc oxide whiskers The gravity effect of fiber improves dispersion uniformity.

Benefits of technology

显著改善了钢纤维在水泥基体中的分散均匀性,增强了结合性能,降低了纤维的重力效应,提高了混凝土的力学性能和耐久性,同时避免了颗粒剥落和结团问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118603A_ABST
    Figure CN119118603A_ABST
Patent Text Reader

Abstract

The invention provides a cement-based composite material mixed with surface modified steel fiber and a preparation method thereof. The cement-based composite material is prepared from the following raw materials: 300 to 750 parts of cement, 60 to 100 parts of fly ash, 80 to 200 parts of silica fume, 40 to 100 parts of mineral powder, 300 to 600 parts of coarse aggregate, 400 to 800 parts of fine aggregate, 10 to 60 parts of zinc oxide whisker, 50 to 200 parts of modified steel fiber, 150 to 200 parts of tap water and 8 to 25 parts of water reducing agent. CaCO3 particles are introduced into the modified steel fibers through surface mineralization treatment, on one hand, a large number of fixed sites are provided, and on the other hand, the fibers are endowed with surface roughness, hydrophilicity and affinity with cement mortar, so that the interfacial compatibility and binding force between the steel fibers and a cement matrix are improved, and the gravity effect of the steel fibers is overcome; and meanwhile, the low-density zinc oxide whiskers replace part of steel fibers, so that the gravity effect is also reduced. In addition, the dense filling effect of the zinc oxide whiskers further improves the internal microstructure of the concrete, reduces the generation of gaps, and improves the compactness of the concrete. According to the invention, the reinforced and toughened cement-based composite material with uniformly dispersed fibers is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to a cement-based composite material mixed with surface-modified steel fibers and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete (UHPC), as a cement-based composite material with excellent mechanical properties and good durability, is one of the most widely used building materials in construction projects. The uniform distribution of steel fibers in the cement matrix is ​​a prerequisite for the enhancement and toughening of UHPC. If the fibers are unevenly dispersed, the reinforcing effect of the fiber mesh skeleton when UHPC is subjected to specific loads will be greatly reduced, and stress will be difficult to effectively transfer from the matrix to the fibers, resulting in stress concentration, the development of microcracks, and the generation of macrocracks inside the concrete, thereby affecting its service life. The current UHPC system cannot fully utilize the reinforcement effect of steel fibers, the toughness of the matrix is ​​not improved enough, and it still has poor brittle characteristics when destroyed.

[0003] The existing evaluation and control technologies for the uniformity of steel fiber dispersion focus mainly on the composition and ratio of raw materials, the volume ratio of steel fibers, or the mixing and vibration molding under processing conditions. However, due to the smooth surface and surface inertness of steel fibers, the surface still has a certain degree of hydrophobicity after anti-rust treatment of the coating, so the bonding between them and the UHPC matrix is ​​relatively poor, and the interface is the first to debond under stress; the gravity effect of the fiber causes the fiber to be distributed sparsely on the top and densely on the bottom in the concrete. Therefore, starting from challenging the surface properties of steel fiber materials, improving its interfacial compatibility and bonding with the UHPC matrix to overcome the gravity effect of steel fibers is one of the new research directions for improving the dispersion of steel fibers in UHPC.

[0004] The main methods to improve the bonding performance between steel fibers and UHPC matrix are: 1) regulating the type and density of surface charge, such as chemical methods such as adding electrolytes and surfactants or physical methods such as changing pH value and heat treatment; 2) regulating the surface energy of fibers, such as surface coating, nanomaterial loading or sandpaper polishing. For example, the Chinese invention patent application entitled "A method for surface modification of steel fibers" with application number 202311169850.X uses self-polymerizing and oxidizing dopamine to form a polydopamine coating on the surface of steel fibers to enhance its bonding strength with the interface. However, dopamine is expensive; it is easily oxidized in the air, which is not convenient for storage and transportation. It is necessary to conduct further improvement research based on the surface characteristics of steel fibers. Summary of the invention

[0005] In view of the defects or shortcomings of the prior art, the present invention aims to provide a cement-based composite material mixed with surface-modified steel fibers, based on the functional modification of the surface of the steel fiber material and the introduction of nanoparticles through layer-by-layer mineralization, thereby improving the surface properties of the material and improving the uniformity of steel fiber dispersion.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A cement-based composite material mixed with surface-modified steel fiber, wherein the raw materials include, by weight, 300-750 parts of cement, 60-100 parts of fly ash, 80-200 parts of silica fume, 40-100 parts of mineral powder, 300-600 parts of coarse aggregate, 400-800 parts of fine aggregate, 10-60 parts of zinc oxide whisker, 50-200 parts of modified steel fiber, 150-200 parts of tap water, and 8-25 parts of water reducer;

[0008] The steel fiber has been subjected to surface mineralization modification treatment, the steps of which are as follows:

[0009] S1: Pretreatment of steel fiber: The steel fiber is cleaned with a neutral detergent, ethanol and water in sequence, and dried to obtain clean steel fiber;

[0010] S2: Surface mineralization modification of steel fiber: The clean steel fiber is immersed in an aqueous solution of biophenolic hydroxy acid, and the steel fiber is taken out and washed with deionized water; then the steel fiber is immersed in a CaCl2 solution and a Na2CO3 solution at room temperature in turn, and the steel fiber is shaken on a shaker during the immersion process. After the immersion is completed, the steel fiber is taken out and washed with deionized water; after repeating the operation of alternating immersion in CaCl2 solution and Na2CO3 solution and washing with deionized water for 1 to 4 times, the steel fiber is dried to constant weight, and the modified steel fiber is obtained after cooling.

[0011] Preferably, the biological phenolic hydroxy acid is at least one of phytol acid and phytol acid; the phytol acid includes at least one of phytic acid, alginic acid and tartaric acid; the phytol acid includes at least one of tannic acid and flavanols; the flavanols include at least one of gallic acid, epicatechin, epigallocatechin, epicatechin gallate and epigallocatechin gallate.

[0012] Preferably, the biological phenolic hydroxy acid is at least one of tannic acid, phytic acid, gallic acid and alginic acid; more preferably, phytic acid and tannic acid.

[0013] Preferably, the concentration of the biophenolic hydroxy acid solution is 0.1-2.0 wt %; the concentration of the CaCl2 and Na2CO3 aqueous solutions is 0.1-1.0 mol / L, more preferably 0.2-0.5 mol / L.

[0014] Preferably, the immersion conditions of the biophenolic hydroxy acid are 40-80°C, 10-40 min; the immersion time of the CaCl2 and Na2CO3 solutions is 5-30 min, the shaking frequency of the shaker is 20-50 rpm; and the drying temperature of the steel fiber is 50-80°C.

[0015] Preferably, the steel fiber is selected from one or more of straight, hook-end or wavy steel fibers with a diameter of 0.15 to 0.35 mm, an aspect ratio of 40 to 75, and a tensile strength of ≥ 2000 MPa;

[0016] Preferably, the steel fiber is selected from at least one of ordinary steel fiber, copper-plated steel fiber and galvanized steel fiber.

[0017] Preferably, the mass ratio of the zinc oxide whisker to the modified steel fiber is (0.5-3):5; more preferably (1.5-2):5.

[0018] Preferably, the zinc oxide whisker has a four-needle structure, a diameter of 0.5 to 5 μm, and a length of 10 to 50 μm.

[0019] Zinc oxide whiskers are whisker-like crystals that are similar in shape to short fibers but much smaller in size. The addition of zinc oxide whiskers replaces part of the weight of steel fibers and reduces the gravity effect of steel fibers to a certain extent. The four-needle zinc oxide whiskers used are single crystal structures with almost no structural defects and extremely high mechanical strength and elastic modulus. Their special three-dimensional four-needle structure gives them an isotropic reinforcement effect, making it easier to achieve uniform distribution in the cement matrix and give cement-based composite materials enhanced toughness.

[0020] The present invention also provides a method for preparing a cement-based composite material mixed with surface-modified steel fibers, which is characterized by comprising the following steps:

[0021] Firstly, cement, fly ash, silica fume, mineral powder and zinc oxide whisker are added into a mixer and stirred for 3-4 minutes; then water and water reducing agent are added and stirred for 3-4 minutes to obtain a uniform wet mixture; modified steel fibers are added one by one and stirred for 1-2 minutes, followed by molding, vibrating, molding and curing to obtain the cement-based composite material.

[0022] Biophenolic hydroxy acid is one of the most widely distributed substances in the plant kingdom. It contains a large amount of hydroxyl groups and can be used as a chelating agent to chelate with metal ions to form a stable metal complex. The present invention uses the metal on the surface of the steel fiber (iron or copper or zinc contained in the plated metal steel fiber) as the source of metal ions and utilizes the coordination of hydroxyl groups and metal ions to first complete the functional modification of the biophenolic hydroxyl acid on the surface of the steel fiber. The added Ca 2+ Further cross-linking with biological phenolic hydroxy acids forms a stable double-layer complex network;2+ With CO3 2- The alternating deposition of CaCO3 nanoparticles realizes the interlaced growth of CaCO3 nanoparticles in the complex network; 2+ As well as the strong composite network entanglement structure formed by the iron / copper / zinc on the fiber surface and the biological phenolic hydroxy acid, the deposited particles can be tightly anchored on the fiber.

[0023] The introduction of nanoparticles can, on the one hand, provide a large number of fixed sites to promote the adhesion of cement mortar; the good affinity of CaCO3 particles and cement mortar is conducive to enhancing the bonding strength between steel fibers and cement mortar substrates. On the other hand, the deposited particles give the fiber surface roughness and hydrophilicity, and the friction between steel fibers and cement mortar increases during the raw material mixing process. Steel fibers are more easily dragged to various parts of the concrete raw material mixture with the flow of cement mortar, and are more evenly dispersed.

[0024] Beneficial effects of the present invention:

[0025] The technical solution of the present invention starts from adjusting the material properties of steel fibers, performs functional modification of biophenolic hydroxy acids on the surface of steel fibers, and introduces nanoparticles through layer-by-layer mineralization treatment to enhance the interfacial bonding stress between the steel fibers and the cement matrix, thereby overcoming the gravity effect of some steel fibers and improving the uniformity of dispersion of the steel fibers in the cement matrix; and the chemical bonds of the complex network strengthen the stability of the combination of the two.

[0026] The present invention adopts an in-situ growth CaCO3 addition method, which can effectively avoid the problem of particle peeling or agglomeration that occurs when conventional external particles are added. The accumulated growth of CaCO3 particles can increase the surface area and active sites of the fiber, increase the contact and friction between the steel fiber and the cement mortar; and give the fiber surface physical roughness and hydrophilicity, which promotes its more uniform dispersion. At the same time, the pre-deposition of biophenolic hydroxyl acid on the steel fiber also gives the steel fiber surface hydroxyl and other hydrophilic polar groups, further improving the wettability and facilitating the adhesion of the cementitious material on the steel fiber surface during the hydration process.

[0027] When biological phenolic hydroxy acid is complexed on the metal surface, it forms a dense monomolecular protective film on the metal surface, which can also effectively prevent oxygen and other substances from contacting the metal surface and resist the corrosion of steel fibers.

[0028] The addition of zinc oxide whiskers, on the one hand, can play its dense filling effect, improve the internal microstructure of steel fiber concrete, refine the pore structure, achieve concrete densification and reduce porosity; at the same time, reduce the surface tension and additional pressure of water in the capillaries, and reduce the drying shrinkage of concrete; micron-scale zinc oxide whiskers can also wrap particles and penetrate into the cement matrix to prevent crack propagation, and enhance the physical adhesion with the cement matrix. On the other hand, zinc oxide whiskers replace part of the weight of steel fibers, reducing the gravity effect of steel fibers to a certain extent. In addition, zinc oxide materials themselves have strong radiation shielding and radio wave absorption functions, which can enhance the radiation protection and antistatic effects of UHPC. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is the steel fiber pulling load-slip curve of comparative example 1 and embodiment 1, embodiment 3 and embodiment 4. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention will be further described in detail below through specific implementation, but the implementation of the present invention is not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0031] The sheared copper-plated steel fibers and ordinary steel fibers had the same technical parameters: diameter 0.2 mm, length 13 mm, tensile strength 2850 MPa, purchased from Shanghai Qingbei New Materials Technology Co., Ltd.;

[0032] Tannic acid, gallic acid, alginic acid, AR, were purchased from Aladdin Reagent Company; phytic acid (50%), anhydrous calcium chloride, anhydrous sodium carbonate, AR, were purchased from MacLean Reagent Company;

[0033] Zinc oxide whiskers, with a diameter of 0.5-5 μm and a length of 10-50 μm, were purchased from Hangzhou Jikang New Materials Co., Ltd.;

[0034] Conch brand P·Ⅱ52.5 silicate cement has a measured strength of 62.5MPa and a specific surface area of ​​360m 2 / kg;

[0035] Class F, Grade I power plant fly ash, with a specific surface area of ​​440m 2 / kg, Guangzhou Hengyun Thermal Power Co., Ltd.;

[0036] Silica fume, SiO2 content ≥ 95%, water content ≤ 2%, Gansu Yuyang New Materials Co., Ltd.;

[0037] S95 mineral powder, specific surface area is 450m 2 / kg, density is 2.6g / cm3 , Lingshou County Shengbang Mineral Products Processing Plant;

[0038] Polycarboxylate water reducer, solid content 40%, water reduction rate 25-45%, Sika (China) Co., Ltd.;

[0039] The coarse aggregate is washed, dried and continuously graded Class I construction crushed stone with a particle size of 5 to 8 mm and a mud content of ≤0.5%;

[0040] The fine aggregate is continuously graded medium sand with a fineness modulus of 2.5 and a mud content of ≤0.5%.

[0041] Example 1

[0042] A cement-based composite material mixed with surface-modified steel fibers, firstly preparing the modified steel fibers, the specific process is as follows:

[0043] S1: Pretreatment of steel fiber: Use neutral detergent to remove stains from steel fiber, use alcohol to degrease steel fiber, use warm water to remove residual alcohol and detergent, and dry to obtain clean steel fiber;

[0044] S2: Surface mineralization modification of steel fibers:

[0045] 50 parts of clean steel fibers were immersed in 200 parts of 2.0wt% tannic acid solution at 60°C for 30 minutes, and then washed with deionized water to remove residual tannic acid molecules;

[0046] The steel fiber was immersed in 0.5mol / L CaCl2 solution and 0.5mol / L Na2CO3 solution for 15min and 10min respectively. The immersion conditions were room temperature and shaking on a shaker with a shaking frequency of 30rpm. After each immersion, the steel fiber was taken out and washed with deionized water to remove excess substances. After repeating the operation of alternating immersion in CaCl2 solution and Na2CO3 solution and washing with deionized water twice, the steel fiber was dried at 60°C to obtain modified steel fiber.

[0047] Secondly, a cement-based composite material mixed with surface-modified steel fiber is prepared, and the raw materials include: cement, fly ash, silica fume, sand, stone, the above-mentioned modified steel fiber, water and water reducing agent. The raw material components are weighed according to the mix ratio shown in Table 1; a forced mixer (maximum mixing capacity is 60L) is used to mechanically stir each mortar material at a speed of 50r / min: first, cement, fly ash, silica fume, mineral powder, and zinc oxide whisker are added to the mixer and stirred for 3 to 4 minutes; then water and water reducing agent are added, and stirring is continued for 3 to 4 minutes until the wet mixing is uniform; finally, the modified steel fiber is added one by one, and stirring is carried out for 1 to 2 minutes to obtain a fresh UHPC mixture.

[0048] Table 1 UHPC raw material ratio in Example 1 (parts by weight)

[0049]

[0050] Example 2-Example 4

[0051] The operation is the same as in Example 1, except that the steel fiber is alternately immersed in the CaCl2 solution and the Na2CO3 solution for 1, 3, and 4 times respectively.

[0052] Example 5-Example 6

[0053] The operation is the same as that of Example 1, except that in step S2, the steel fiber is immersed in the CaCl2 solution and the Na2CO3 solution with concentrations of 0.2 mol / L and 1.0 mol / L respectively.

[0054] Example 7-Example 9

[0055] The operation is the same as that of Example 1, except that the tannic acid in step S2 is replaced by phytic acid, gallic acid, and alginic acid, respectively.

[0056] Example 10-Example 12

[0057] The operation is the same as in Example 1, except that the mass ratios of zinc oxide whisker to modified steel fiber are 1:5, 2:5 and 3:5, respectively, that is, the steel fiber dosage is fixed, and the zinc oxide whisker is 20 parts, 40 parts and 60 parts, respectively.

[0058] Embodiment 13

[0059] The operation is the same as in Example 1, except that the steel fiber is replaced with copper-plated steel fiber.

[0060] Comparative Example 1

[0061] The operation is the same as that of Example 1, except that step S2 is omitted, that is, the steel fiber is not subjected to surface modification treatment, and a steel fiber reinforced cement-based composite material is prepared.

[0062] Comparative Example 2

[0063] The operation is the same as in Example 1, except that the mineralization deposition treatment of the steel fiber is omitted, that is, the steel fiber is only impregnated with the tannic acid solution.

[0064] Comparative Example 3

[0065] The operation is the same as in Example 1, except that the impregnation treatment with the tannic acid solution is omitted, that is, the surface mineralization modification of the steel fiber is directly performed.

[0066] Comparative Example 4

[0067] The operation is the same as in Example 1, except that zinc oxide whiskers in the concrete are removed during the preparation of the cement-based composite material.

[0068] For the UHPC mixtures obtained in all the above examples and comparative examples, their pressure water bleeding rates were first measured.

[0069] Compressive strength: The specimen size is 100mm×100mm×100mm, and the test is carried out in accordance with the relevant provisions of standard GB / T50081-2019;

[0070] Flexural strength: The specimen size is 100mm×100mm×400mm, and the test is carried out in accordance with the relevant provisions of standard GB / T50081-2019;

[0071] Since copper-plated steel fibers with poor magnetic properties are used in some embodiments, it is impossible to determine the fiber orientation using the electromagnetic induction method; therefore, the fiber distribution is quantitatively evaluated using the fiber dispersion coefficient β. The specific process includes:

[0072] (1) X-ray micro-computed tomography was used to detect the distribution of steel fibers in concrete. The number of all fibers in the specimen sample area was counted and the average value μ was obtained.

[0073] (2) Divide the sample area in the obtained three-dimensional image and count the number of fibers x in the i-th grid unit in the n grids. i , calculate the coefficient of variation of fiber distribution

[0074]

[0075] μ——the average number of fibers contained in the specimen; x i ——The number of fibers contained in the i-th unit after the specimen is divided into n units; n——The total number of regions divided into the specimen.

[0076] (3) The obtained coefficient of variation is used to calculate the fiber dispersion coefficient β, which is a quantitative indicator describing the uniformity of fiber dispersion in concrete:

[0077]

[0078] In theory, when the mesh is fully filled with fibers, x i =1; in fact, when x i ∈[0.6, 1], indicating that the area has been mostly filled with dispersed fibers and can be regarded as a whole with adjacent units with similar fiber numbers to form a fiber bundle. i=0 means that there is only cement in the area, no fiber, and it may also mean that the fibers in the adjacent area may be clustered or lumped. When the number of fibers in each unit in the pattern is equal, that is, the steel fibers are evenly distributed, Φ = 0, β = 1; if one unit concentrates all the steel fibers, and the number of steel fibers in other units is 0, then Φ → ∞, β = 0.

[0079] The test results of the concrete test blocks of various embodiments and comparative examples are shown in Table 2.

[0080] Table 2 Test results of concrete of each embodiment and comparative example

[0081] sample Pressure water seepage rate / % Flexural strength / MPa 28d compressive strength / MPa Fiber dispersion coefficient β Example 1 20.9 25.1 174 0.696 Example 2 22.6 22.5 163 0.61 Example 3 19.5 27.3 183 0.749 Example 4 19.9 26.9 181 0.74 Example 5 22.9 22.1 161 0.592 Example 6 20.6 26.2 178 0.722 Example 7 20.5 25.8 176 0.71 Example 8 21.1 24.3 172 0.685 Example 9 22 23 169 0.65 Example 10 20.6 24.3 167 0.659 Embodiment 11 18.9 26.6 173 0.734 Example 12 21.6 27.5 165 0.687 Embodiment 13 21.2 26.2 170 0.691 Comparative Example 1 24.3 19.1 147 0.542 Comparative Example 2 23.5 21.3 153 0.563 Comparative Example 3 24 19.7 148 0.548 Comparative Example 4 22.3 22.8 165 0.622

[0082] Compared with Comparative Example 1, the steel fibers in Examples 1 to 4 were subjected to surface mineralization modification with different deposition times, and the pressure water bleeding rate of the obtained fresh mixture was significantly reduced, and the dispersion coefficient of the cement-based composite material was improved. This is because the surface distribution density and area of ​​the accumulated calcium carbonate on the surface of the steel fiber increased, which provided contact sites with the cementitious material, making the pure slurry and steel fiber mixed more evenly; the improvement of the roughness and hydrophilicity of the steel fiber reduced the volume of free water in the calcium carbonate and cement matrix, reduced the water bleeding rate, and made the mechanical performance more prominent. However, if the deposition times are too many, as shown in Example 4, the mechanical properties will decrease slightly, which means that the deposition layer of calcium carbonate particles is too thick, so that the contact with water is not sufficient during mixing, resulting in an increase in internal defects and voids in the concrete, thereby increasing free water, making the mixture slurry more prone to water bleeding, and the dispersibility of the steel fiber also deteriorates. The number of calcium carbonate deposition times is more preferably 2 to 3 times.

[0083] Further, the single fiber pull-out test was performed on the embodiment with different deposition times and the comparative example 1. Figure 1 The typical pull-out load-slip curve of steel fiber is shown. In the initial good bonding area stage, the slopes of the load-slip curves of different samples are similar. The pull-out load rises sharply, while the slip increases only slightly. The load and slip are in a linear elastic relationship. In the subsequent partial peeling area, the load-slip curve shows a nonlinear relationship, and as the degree of calcium carbonate deposition increases, the corresponding peak load also gradually increases, and the required pull-out energy also increases; among them, the strengthening trend of Examples 3 and 4 with deposition times of 3 and 4 is obvious. This is the result of the increased bonding force between the steel fiber and the cement matrix. The pull-out energy of Example 4 is slightly less than that of Example 3, which shows that the excessive thickness of calcium carbonate deposition reduces the bonding strength, resulting in the appearance of cracks and the decline of mechanical properties, which is consistent with the results presented in Table 2.

[0084] Example 5 is a second deposition of calcium carbonate particles on the steel fiber surface at a lower deposition concentration (0.2 mol / L), and its mechanical property results are similar to those of Example 2 (i.e., a single deposition at a concentration of 0.5 mol / L); Example 6 has the same theoretical deposition amount as Example 4, i.e., two depositions at a concentration of 1 mol / L and four depositions at a concentration of 0.5 mol / L, respectively, but the mechanical properties of Example 6 are worse. This proves that the efficiency of multiple depositions at low concentrations is better than that of single depositions at high concentrations. Therefore, the calcium carbonate deposition concentration can be further optimized to 0.2-0.5 mol / L.

[0085] Combined with Example 1, Example 7-Example 9, there are differences in the strength of the four biological phenolic hydroxy acids and metal complexing forces. Furthermore, phytic acid>tannic acid>gallic acid>alginic acid, so there are obvious differences in the efficiency and density of their functional modification of steel fibers, which in turn affects the number and area of ​​subsequent in-situ growth points of calcium carbonate, resulting in different dispersion effects and mechanical properties. Phytic acid is a polyanionic chelating agent with 12 polarizable acid protons and 6 negatively charged phosphate groups, and has a strong complexing ability; tannic acid has multiple ortho-phenolic hydroxyl structures, which can be used as a polyhydroxy ligand to react with metal ions, and two adjacent phenolic hydroxyl groups can form a stable five-membered ring chelate with metal ions in the form of oxygen anions.

[0086] On the whole, the preferred biological phenolic hydroxy acids are phytic acid and tannic acid.

[0087] In combination with Example 1, Example 10-Example 12 and Comparative Example 4, the dosage of zinc oxide whiskers will also affect its composite effect with modified steel fibers, and thus affect the mechanical strength of concrete. The cement-based composite material of Comparative Example 4 without zinc oxide whiskers has good mechanical strength but limited improvement in its dispersibility; when a small amount of zinc oxide whiskers is added, that is, when the ratio of zinc oxide whiskers to modified steel fibers is low, the fluidity and dispersibility of the cement paste are not significantly weakened, and it has a significant strengthening and toughening effect; as the dosage of zinc oxide whiskers increases, although the flexural strength continues to increase, the compressive strength of the concrete is significantly deteriorated. The dosage range of zinc oxide whiskers / modified steel fibers is further preferably (1.5-2):5.

[0088] The results of Example 1 and Example 13 prove that the surface hydroxyl functionalization and mineralization modification treatment method of steel fiber provided by the present invention has universal applicability. Furthermore, Example 13 is slightly inferior to Example 1 in mechanical performance and dispersibility, because the complexation speed and strength of tannic acid and high-valent metal iron are better than those of divalent metal copper.

[0089] The results of Comparative Examples 2 and 3 show that the hydroxy acid functional modification and mineralization modification of the steel fiber surface provided by the present invention have additive effects on the optimization of steel fiber and concrete. Comparative Example 2 is a single functional modification of biophenolic hydroxy acid, which can only form a protective film, which has limitations in improving the dispersibility of steel fiber in concrete; while Comparative Example 3 is only a mineralization treatment, and the inert steel fiber surface lacks its attachment growth point, so the growth efficiency and firmness drop sharply.

[0090] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A cement-based composite material mixed with surface-modified steel fibers, characterized in that: By weight, the raw materials include 300-750 parts of cement, 60-100 parts of fly ash, 80-200 parts of silica fume, 40-100 parts of mineral powder, 300-600 parts of coarse aggregate, 400-800 parts of fine aggregate, 10-60 parts of zinc oxide whisker, 50-200 parts of modified steel fiber, 150-200 parts of tap water, and 8-25 parts of water reducer; The modified steel fiber is subjected to surface mineralization modification treatment, and the steps are as follows: S1: Pretreatment of steel fiber: The steel fiber is cleaned with a neutral detergent, ethanol and water in sequence, and dried to obtain clean steel fiber; S2: Surface mineralization modification of steel fiber: The clean steel fiber is immersed in an aqueous solution of biophenolic hydroxy acid, and the steel fiber is taken out and washed with deionized water; then the steel fiber is immersed in a CaCl2 solution and a Na2CO3 solution at room temperature in turn, and the steel fiber is shaken on a shaker during the immersion process. After the immersion is completed, the steel fiber is taken out and washed with deionized water; after repeating the operation of alternating immersion in CaCl2 solution and Na2CO3 solution and washing with deionized water for 1 to 4 times, the steel fiber is dried to constant weight, and the modified steel fiber is obtained after cooling.

2. The cement-based composite material according to claim 1, characterized in that: The biological phenolic hydroxy acid is at least one of plant alcohol acid and plant phenolic acid; the plant alcohol acid includes at least one of phytic acid, alginic acid and tartaric acid; the plant phenolic acid includes at least one of tannic acid and flavanols; the flavanols include at least one of gallic acid, epicatechin, epigallocatechin, epicatechin gallate and epigallocatechin gallate.

3. The cement-based composite material according to claim 2, characterized in that: The biological phenolic hydroxy acid is at least one of phytic acid and tannic acid.

4. The cement-based composite material according to claim 1, characterized in that: The steel fibers are selected from one or more of straight, hook-end or wavy steel fibers with a diameter of 0.15-0.35 mm, an aspect ratio of 40-75, and a tensile strength of ≥2000 MPa.

5. The cement-based composite material according to claim 1, characterized in that: The steel fiber is selected from at least one of ordinary steel fiber, copper-plated steel fiber and galvanized steel fiber.

6. The cement-based composite material according to claim 1, characterized in that: The concentration of the biological phenolic hydroxy acid solution in step S2 is 0.1-2.0 wt %; the concentration of the CaCl 2 and Na 2 CO 3 aqueous solutions is 0.1-1.0 mol / L.

7. The cement-based composite material according to claim 1, characterized in that: In step S2, the immersion conditions of the biophenolic hydroxy acid are 40-80°C for 10-40 minutes; the layer-by-layer immersion time of the CaCl2 and Na2CO3 solutions is 5-30 minutes; the shaking frequency of the shaker is 20-50rpm; and the steel fiber drying temperature is 50-80°C.

8. The cement-based composite material according to claim 1, characterized in that: The mass ratio of the zinc oxide whisker to the modified steel fiber is (0.5-3):

5.

9. The cement-based composite material according to claim 1, characterized in that: The zinc oxide whisker has a diameter of 0.5-5 μm and a length of 10-50 μm.

10. The method for preparing a cement-based composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Firstly, cement, fly ash, silica fume, mineral powder and zinc oxide whisker are added into a mixer and stirred for 3-4 minutes; then water and water reducing agent are added and stirred for 3-4 minutes to obtain a uniform wet mixture; modified steel fibers are added one by one and stirred for 1-2 minutes, followed by molding, vibrating, molding and curing to obtain the cement-based composite material.

Citation Information

Patent Citations

  • Basalt fiber surface modification method

    CN114477797A

  • Lightweight high-strength concrete and preparation method thereof

    CN115057671A

  • Building floor light-weight heat-preservation sound-insulation self-leveling mortar and preparation method thereof

    CN115417691A

  • Rust-proof steel fiber concrete and preparation method thereof

    CN115925335A

  • Double-network polymer in-situ toughened cement-based material and preparation method thereof

    CN117125938A